2018
DOI: 10.1016/j.puhe.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between National Health Service trusts' clinical trial activity and both mortality rates and care quality commission ratings: a retrospective cross-sectional study

Abstract: The mortality-related results corroborate with other published data showing a correlation between increased research and reduced deaths. Furthermore, there is also a statistically significant association between clinical trials activity and improved CQC ratings. However, these tie-ins are predominantly driven by the number of participants in interventional research rather than observational research activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 21 publications
3
74
0
2
Order By: Relevance
“…Research-active National Health Service (NHS) organisations in the United Kingdom are associated with improved outcomes in patient and staff experience compared to their less active counterparts (Jonker and Fisher 2018;Jonker et al, 2019). The introduction of research training programmes, such as the NIHR Integrated Clinical Academic Training (NIHR ICA) programme, provides NHS Trusts with vital funding on which to build a sustainable culture for research activity, specifically supporting clinical academic training for NMAHP professions.…”
Section: Introductionmentioning
confidence: 99%
“…Research-active National Health Service (NHS) organisations in the United Kingdom are associated with improved outcomes in patient and staff experience compared to their less active counterparts (Jonker and Fisher 2018;Jonker et al, 2019). The introduction of research training programmes, such as the NIHR Integrated Clinical Academic Training (NIHR ICA) programme, provides NHS Trusts with vital funding on which to build a sustainable culture for research activity, specifically supporting clinical academic training for NMAHP professions.…”
Section: Introductionmentioning
confidence: 99%
“…There is an associated link between clinical research engagement and improved patient outcomes. 1 Not only does this apply to the subjects of research but also to those patients who are not active participants but are treated at sites where research is conducted. 2 Unfortunately, clinical research activity is not uniformly spread across the country.…”
Section: A Haemstar Is Born; a Trainee-led Uk-wide Research Network mentioning
confidence: 99%
“…In a retrospective study of 129 hospital Trusts in England NIHR study activity data, summary hospital-level mortality indicator scores and Care Quality Commission (CQC) ratings were analysed adjusting for clinical staffing levels in each Trust. A significant association between the number of studies and participants with summary hospital-level mortality and CQC ratings was observed with correlations between the number of participants recruited into interventional studies especially strong (Jonker, 2018). Although this emerging evidence is not specific to surgery there has been one study which examined outcomes following colorectal cancer surgery and Trust research activity which shows similar findings (Downing 2017).…”
mentioning
confidence: 98%
“…All these activities and initiatives may lead to improvements in patient health and surgery although specific evidence to support this is yet to materialise. There is, however, growing evidence to suggest that participation in research in general improves outcome (Ozdemir 2015, Jonker 2018, Downing 2017.…”
mentioning
confidence: 99%